A technique for relative quantitation of cancer biomarkers in formalin‐fixed, paraffin‐embedded (FFPE) tissue using stable‐isotope‐label based mass spectrometry imaging (SILMSI). (24th July 2015) - Wang, Hong; DeGnore, Jon P.; Kelly, Brian D.; True, Jan; Garsha, Karl; Bieniarz, Christopher
Abstract : We developed a novel technique for the relative quantitation of pairs of cancer biomarkers in formalin‐fixed paraffin‐embedded (FFPE) tissue. The method utilizes stable isotope labeled (SIL) chromogens deposited during the standard immunohistochemistry (IHC) tissue staining process. The labeled chromogens are precipitated on tissue enzymatically using the standard IHC protocols. The tissue is then imaged with matrix‐free laser desorption ionization time‐of‐flight mass spectrometry, and peak intensities of reporter ions are used to estimate the relative quantitation of protein biomarkers across the tissue. The relative abundance of two breast cancer biomarkers, estrogen receptor (ER) and progesterone receptor (PgR), were quantitated using their ratio of expression in xenograft models, and the ratios were found to be reproducible both within and across serial sections. The relative quantification of multiple biomarkers in situ across a single tissue section adds an additional dimension in cancer histological evaluation by allowing a visual and statistical assessment of tumor heterogeneity. Copyright © 2015 John Wiley & Sons, Ltd.